2004
DOI: 10.1152/ajprenal.00135.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ENaC by intracellular Clin an MDCK clone with high ENaC expression

Abstract: We examined the effects of intracellular Cl− concentration ([Cl−]i) on the epithelial Na channel (ENaC) in a line of Madin-Darby canine kidney (MDCK) cells (FL-MDCK) with a high rate of Na+ transport produced by stable retroviral transfection with rENaC subunits (Morris RG and Schafer JA. J Gen Physiol 120: 71–85, 2002). Treatment with cAMP (100 μM 8-cpt-cAMP plus 100 μM IBMX) stimulated ENaC-mediated Na+ absorption as well as Cl− secretion via cystic fibrosis transmembrane conductance regulator, which was cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 60 publications
5
28
0
Order By: Relevance
“…In that study, [Cl ) ] i was assessed using the Cl ) -sensitive fluorescence dye 6-methoxy-N-(3-sulphopropyl)quinolinium (SPQ). In MDCK cell monolayers, grown polarized and basolaterally permeabilized, Xie and Scha¨fer found a large change in [Cl ) ] i following cAMP-dependent stimulation, although in this case [Cl ) ] i decreased from 76 to 36 mM [34], rather than increasing, as in our study. While the principle finding of that study, that an increase in [Cl ) ] i inhibits ENaC, is in good agreement with our findings, the decrease in [Cl ) ] i elicited by cAMP-dependent stimulation is rather surprising.…”
Section: Inhibition Of Enac By [Cl ) ] Isupporting
confidence: 60%
See 1 more Smart Citation
“…In that study, [Cl ) ] i was assessed using the Cl ) -sensitive fluorescence dye 6-methoxy-N-(3-sulphopropyl)quinolinium (SPQ). In MDCK cell monolayers, grown polarized and basolaterally permeabilized, Xie and Scha¨fer found a large change in [Cl ) ] i following cAMP-dependent stimulation, although in this case [Cl ) ] i decreased from 76 to 36 mM [34], rather than increasing, as in our study. While the principle finding of that study, that an increase in [Cl ) ] i inhibits ENaC, is in good agreement with our findings, the decrease in [Cl ) ] i elicited by cAMP-dependent stimulation is rather surprising.…”
Section: Inhibition Of Enac By [Cl ) ] Isupporting
confidence: 60%
“…Inhibition of ENaC by increased intracellular Cl ) has also been demonstrated recently in an MDCK cell clone expressing high levels of retrovirally expressed ENaC [34]. In that study, [Cl ) ] i was assessed using the Cl ) -sensitive fluorescence dye 6-methoxy-N-(3-sulphopropyl)quinolinium (SPQ).…”
Section: Inhibition Of Enac By [Cl ) ] Imentioning
confidence: 81%
“…In addition, Kunzelman and collaborators (Konig et al 2001;Kunzelmann 2003) have shown that the inhibitory effect of CFTR can be mimicked by coexpression of other anion channels (ClC-0 and ClC-2) or treatment with amphotericin B, and this effect can be explained by an increase of Cl − currents or an intracellular Cl − ([Cl − ]i). Some authors have been shown that an increase in [Cl − ]i inhibits ENaC activity in FL-MDCK cells (MDCK cells that had been transfected with rat ENaC subunits containing the FLAG epitope in their extracellular loops; Morris and Schafer 2002); however, this effect cannot explain the effect of Cl − secretion on Na + absorption with cAMP treatment because stimulation of Cl − secretion by cAMP results in a fall rather than a rise in [Cl − ]i (Xie and Schafer 2004). Moreover, in the Xenopus oocyte expression system, CFTR activation inhibits ENaC at a continuous holding potential at which CFTR mediates inward currents corresponding to Cl − efflux (Konstas et al 2003).…”
Section: Cftr and Regulation Of Enac Activitymentioning
confidence: 99%
“…Our initial work suggested that influx of Cl Ϫ into the oocyte rather than the efflux is inhibiting ENaC (9). Although a role of Cl Ϫ for the inhibition of ENaC by CFTR was not found in all studies (19,35), subsequent work in both epithelial tissues and Xenopus oocytes confirmed that intracellular Cl Ϫ ions decrease expression of ENaC protein (36) and acutely inhibit ENaC currents (15,27,30,37). Recent studies with polarized epithelial cells expressing ENaC along with CFTR and Ca 2ϩ -activated Cl Ϫ channels, demonstrate an increase in intracellular Cl Ϫ by stimulation of CFTR or Ca 2ϩ -dependent Cl Ϫ channels (38).…”
mentioning
confidence: 94%